Assessing the effectiveness of english camp in enhancing junior high school students' conversational skills - Kaharuddin, Kaharuddin (Educenter : Jurnal Ilmiah Pendidikan, 2025)
This study explores the effectiveness of English language camps in developing junior high school students' conversational skills. In non-English-speaking countries, English language camps are seen as a popular approach to improving English language skills through immersive learning environments. This study employed a case study approach involving junior high school students as research subjects and focused on the effect of immersion learning on speaking and listening skills. Data were collected through pre- and post-camp assessments, observations of learning activities, and interviews with students and teachers. Data analysis was conducted using a quantitative approach to compare the results of pre- and post-program assessments, and a qualitative approach through thematic analysis of the interview and observation results to describe the participants' learning experiences in greater depth. The results showed that the immersive environment in English language camps positively contributed to the development of students' conversational skills, particularly in terms of fluency and vocabulary use. These findings provide important implications for educators and language program managers in designing more effective English language camps, oriented towards communicative practice, and supporting the sustainable development of students' conversational skills.